Evaluation of formal preparation of universities for international mobility. Results of questionnaire research conducted among employees - Kwiatkowska-Ciotucha, Dorota; Załuska, Urszula; Kozyra, Cyprian (Ocena przygotowania formalnego uczelni do międzynarodowej mobilności. Wyniki badań kwestionariuszowych w grupie pracowników, 2021)
The article is dedicated to the evaluation of the formal preparation of universities for international mobility. In order to perform the analysis, the authors used the results of the quantitative primary research conducted in the Stranger project of the Erasmus + strategic partnership. The target group included employees (administrative staff and academic teachers) from universities in Poland, Greece, Hungary and Ukraine that form the partnership. To make it possible for respondents to answer closed-ended questions, summative scales were created. The study examined correlation relationships between the respondents’ answers aggregated to summative scales, and also strived to classify the respondents in terms of the obtained values for summative scales using hierarchical cluster analysis (Ward’s method). The results of the analyses showed the existence of many problems in the field of broadly understood internationalization of universities, and also indicated a significant differentiation of evaluations due to respondents’ characteristics.
Econometrics = Ekonometria, 2021, Vol. 25, No. 1, s. 63-81
Keywords: internationalization of the university; international mobility of students; questionnaire research; statistical analysis; internacjonalizacja uczelni; miedzynarodowa mobilność studentów; badania kwestionariuszowe; analizy statystyczne